PERLINDUNGAN HUKUM TERHADAP KONSUMEN MUSLIM ATAS PEMBERIAN VAKSIN CORONA VIRUS DISEASE 2019 (COVID-19) DITINJAU DARI UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - Edi Gustia Bahri; Arrisman (JOURNAL OF LAW AND NATION, 2025)
Article 28E paragraph (2) of the 1945 Constitution has affirmed the right of every individual to practice their religion, choose education, work, citizenship, residence, and the right to return to the territory of the country. This article affirms that the state grants basic rights to its citizens to embrace religion and worship according to their beliefs. The majority of the Indonesian population is Muslim, which has an obligation to avoid things that are forbidden and consume halal. Law Number 33 of 2014 concerning Halal Product Guarantees mandates that all products circulating in Indonesia must have halal certificates. However, in the COVID-19 vaccination program, the government has not provided a guarantee of the halalness of several types of vaccines such as Astra Zeneca, Johnson and Johnson, Moderna, Novavax Inc, and the Pfizer Inc. And BioNTech vaccines. Problem formulation, What is the Legal Position of Muslim Consumers based on laws and regulations in Indonesia? What is the Legal Protection Given to Muslim Consumers for the Provision of the Corona Virus Disease (COVID-19) Vaccine in Indonesia? The research method used is the Normative legal research method with document study data collection techniques and expert interviews, the data obtained is processed and analyzed using qualitative methods (not using numbers or mathematical formulas). The Republic of Indonesia is not a religious state, but the Republic of Indonesia which is based on Pancasila places religion in an important position, so it is very natural that many laws and court decisions recognize and guarantee the position of a religion including Islam and Muslim consumers in the Republic of Indonesia. Legal protection for Muslim consumers is a right that must be given to Muslim citizens, meanwhile, the state also has a responsibility to protect all its citizens, including providing protection and guarantees for the halal and goodness of the COVID-19 vaccine product (Halalan Toyyiban) several types of COVID 19 vaccines provided and distributed by the Government through the Indonesian Ministry of Health to the Indonesian people, some of which are halal certified, some are not halal certified (haram) and some are even not halal certified / not halal at all. Supervision and Socialization regarding laws and regulations related to Halal Product Guarantee (JPH) need to be massively increased to various interested parties, especially the Government as the Organizer of Halal Product Guarantee, Business Actors, and Consumers.